2017
DOI: 10.1002/2211-5463.12330
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐1 facilitates MSC migration via cleavage of IGF‐2/IGFBP2 complex

Abstract: The specific mechanism underlying the tumor tropism of human mesenchymal stem cells (MSCs) for cancer is not well defined. We previously showed that the migration potential of MSCs correlated with the expression and protease activity of matrix metalloproteinase (MMP)‐1. Furthermore, highly tumor‐tropic MSCs expressed higher levels of MMP‐1 and insulin‐like growth factor (IGF)‐2 than poorly migrating MSCs. In this study, we examined the functional roles of IGF‐2 and MMP‐1 in mediating the tumor tropism of MSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…123 To accomplish the whole process, MSCs rearrange their cytoskeleton through the activation or RhoA 124 and express different types of metalloproteinases in response to chemokine stimulation. 125,126 MSCs could also be recruited to the tumor loci, where they differentiate and support the tumor growth. 93,127 In vitro breast cancer, fibrosarcoma, and glioma cells recruit MSCs by releasing FGF.…”
Section: Physiological Aspect: Msc and Migration Assaysmentioning
confidence: 99%
“…123 To accomplish the whole process, MSCs rearrange their cytoskeleton through the activation or RhoA 124 and express different types of metalloproteinases in response to chemokine stimulation. 125,126 MSCs could also be recruited to the tumor loci, where they differentiate and support the tumor growth. 93,127 In vitro breast cancer, fibrosarcoma, and glioma cells recruit MSCs by releasing FGF.…”
Section: Physiological Aspect: Msc and Migration Assaysmentioning
confidence: 99%
“…MMPs are major regulators of cell migration that do not only act by turnover of extracellular matrix (ECM) proteins but also by affecting growth factors, cytokines, chemokines, and surface proteins [ 65 , 166 , 167 , 168 , 169 , 170 ]. Expression of MMP-1 and MMP-2 has been shown to be essential for the migration of MSCs [ 129 , 171 , 172 , 173 , 174 ]. MCP-3 and HB-EGF were identified as chemotactic factors [ 175 , 176 ], and secretion of MCP-1 by MSCs was described with regard to their enhanced migration [ 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the proliferation/promigration effects of lin28B on MSCs were mediated by the lin28B/IGF-2 signaling pathway, as these effects were abolished when IGF-2 was inhibited genetically. IGF-2, which is a member of the insulin family of polypeptide growth factors, has been shown to be relevant to the regulation of MSC proliferation, migration, and differentiation (Guan et al, 2018;Youssef, Aboalola, & Han, 2017). A previous study reported that lin28A was capable of directly binding to IGF-2 mRNA and increasing its translation efficiency in differentiating muscle cells (Polesskaya et al, 2007).…”
Section: Discussionmentioning
confidence: 99%